Professional Ethics as Social Religation. Towards a Complex Vision for the Research of Ethics in a Professional Level - Juan Martín López Calva (Universidad Autónoma de Baja California, 2010)
Based on a synthetic description of the "state of the art" in the field of "Professional ethics" research and the preliminary results of the "interinstitutional project on professional ethics" that involves 15 universities around the country, this article explores the notion of "social religation" developed by Edgar Morin (2005) as a key term that can help the understanding of "professional ethics" in a new, complex, holistic, dialogical and recursive perspective linked to the other "human religation duties" and always inserted in tensions and contradictions that all the professionals live in their decision making. From this new complex perspective, the article assumes the necessity to transcend the notion of "professional values" as a guide concept in research about "professional ethics" to make new research based on the moral decision making of professionals in a world characterized by the "curl": crisis-change-globalization.